The hero reloaded : the reinvention of the classical hero in contemporary mass media - López Gregoris, Rosario; Macías Villalobos, Cristóbal (IVITRA research in linguistics and literature ;, 2020)
"What was a hero in Classical Antiquity? Why is it that their characteristics have transcended chronological and cultural barriers while they are still role models in our days? How have their features changed to be embodied by comic superheroes and film? How is their essence vulgarized and turned into a mass consumption product? What has happened with their literary and artistic representation along centuries of elitist Western culture? This book aims at posing these and other questions about heroes, allowing us to open a cultural reflection over the role of the classical world in the present, its meaning in mass media, and the capacity of the Greek and Roman civilizations to dialogue with the modern world. This dialogue offers a glimpse into modern cultural necessities and tendencies which can be seen in several aspects, such as the hero's vulnerability, the archetype's banalization, the possibility to extend the heroic essence to individuals in search of identities - vital as well as gender or class identities. In some products (videogames, heavy metal music) our research enables a deeper understanding of the hero's more obvious characteristics, such as their physical and moral strength. All these tendencies - contemporary and consumable, contradictory with one another, yet vigorous above all - acquire visibility by means of a polyhedral vehicle which is rich in possibilities of rereading and reworking: the Greco-Roman hero. In such a virtual and postmodern world as the one we inhabit, it comes not without surprise that we still resort to an idea like the hero, which is as old as the West"--